Revision of the Palaearctic and Oriental representatives of Lachnocrepis LeConte and Oodes Bonelli (Coleoptera: Carabidae), with special account on Chinese species - Guéorguiev, Borislav; Liang, Hongbin (Zootaxa, 2020)
In order to investigate the Chinese representatives from two genera of the tribe Oodini LaFerté-Sénectère, 1851, twenty-three Palaearctic and Oriental species of the genera Lachnocrepis LeConte, 1853 and Oodes Bonelli, 1810 are taxonomically reviewed. Because the species in question share a high degree of morphological similarity they are grouped in the “Oodes generic group”. The character-analysis showed that seven species belong to Oodes, including five species to Oodes s.str. and two species to Lachnocrepis (downgraded to subgenus). The remaining sixteen species are classified in three genera: ten species in Pseudoodes gen. n. (type species: Oodes cribristernis Bates, 1892), two species in Sundaoodes gen. n. (type species: Sundaoodes hainanensis sp. n.), and four species in Nothoodes gen. n. (type species: Oodes angustatus Lorenz, 2005). The taxa of Oodes s.str. and Pseudoodes gen. n. are arranged in two and four species groups, respectively.                Eleven species from three genera, including six new to science, are found in China: Oodes (Oodes) echigonus Habu & Baba, 1960, Oodes (Lachnocrepis) desertus Motschulsky, 1858, Oodes (Lachnocrepis) japonicus (Bates, 1873), Pseudoodes cribristernis (Bates, 1892) (first record for China), Pseudoodes rambouseki (Jedlička, 1931), Pseudoodes ampliusculus, sp. n. (type locality: Mingfenggu Valley, Jiangfengling Mountains, Hainan), Pseudoodes emeishanicus, sp. n. (type locality: Xixinsuo Temple, Emei Shan, Leshan City, Sichuan), Pseudoodes hunanensis, sp. n. (type locality: Xiaozhuangping, Tianping Shan, Sangzhi County, Hunan), Pseudoodes leigongshanicus, sp. n. (type locality: Xijiang Town, Leigong Shan, Leishan County, Guizhou), Pseudoodes tianlinensis, sp. n. (type locality: Cenwanglao Shan, Tianlin County, Guangxi), and Sundaoodes hainanensis, sp. n. (type locality: Nada Town, Danzhou City, Hainan). Two further new species, Sundaoodes kalimantanensis, sp. n. (type locality: Bukit Liang Mount, West Kalimantan Province, Indonesia) and Nothoodes bharat, sp. n. (type locality: Dwarakapuram Village, Naidupet Mandal, Nellore District, Andhra Pradesh, India), are also described.                The following new synonymies are proposed: Oodes parallelus Motschulsky, 1858, syn. n. of Oodes helopioides (Fabricius, 1792); Oodes parallelogrammus Motschulsky, 1858, syn. n. of Oodes helopioides (Fabricius, 1792); Oodes prolixus Bates, 1873, syn. n. of Oodes desertus Motschulsky, 1858; Simous viridissimus Louwerens, 1951, syn. n. of Pseudoodes coelestinus (Chaudoir, 1882). The synonymy of Oodes hahni Reitter, 1908 with Oodes desertus Motschulsky, 1858 is confirmed. Also, the following new combinations are introduced: Oodes japonicus (Bates, 1873), comb. n. of Lachnocrepis japonica Bates, 1873; Pseudoodes vicarius (Bates, 1873), comb. n. of Oödes vicarius Bates, 1873; Pseudoodes coelestinus (Chaudoir, 1882), comb. n. of Oodes coelestinus Chaudoir, 1882; Pseudoodes subcoriaceus (Chaudoir, 1882), comb. n. of Oodes subcoriaceus Chaudoir, 1882; Pseudoodes cribristernis (Bates, 1892), comb. n. of Oodes cribristernis Bates, 1892; Pseudoodes rambouseki (Jedlička, 1931), comb. n. of Holosoma rambouseki Jedlička, 1931; Nothoodes taprobanae (Andrewes, 1923), comb. n. of Oodes taprobanae Andrewes, 1923; Nothoodes longus (Andrewes, 1940), comb. n. of Oodes longus Andrewes, 1940; Nothoodes angustatus (Lorenz, 1998), comb. n. of Oodes angustatus Lorenz, 1998. Lectotypes are designated for Oodes parallelus Motschulsky, 1858, Oodes parallelogrammus Motschulsky, 1858, Oodes desertus Motschulsky, 1858, Oodes cribristernis Bates, 1892, Oodes hahni Reitter, 1908, Oodes thessalonicensis Schatzmayr, 1909, Oodes helopioides var. fiorii Porta, 1923, and Holosoma rambouseki Jedlička, 1931.                A key to the species, diagnoses, descriptions, notes on type specimens, relationships, distribution, bionomics when available, and figures of body, genitalia and other characters useful for taxonomy are provided. Numerous new records, including first country records for Romania, Israel, Nepal, China, Thailand, Laos, Vietnam, Brunei, and Indonesia, are registered.